Land Suitability of The Pas Ipa Beach Tourims, Mangoli Barat Subdistrict, Sula Islands Regency - Pasongli, Hernita; Salam, Ramdani; Tempola, Wahyudi (LaGeografia, 2021)
Tourism is one of the most important sectors in Indonesia after oil, natural gas and palm oil. The development of tourism in Indonesia is currently growing rapidly. This is because the tourism sector is very promising and provides benefits to many parties from the government, the public and the private sector. One of the special tourism objects in the West Mangoli sub-district of Sula Islands, North Maluku province is the Pas Ipa beach, however, the Pas Ipa beach tourism object has never been evaluated as an academic base for future development. This research uses descriptive quantitative method. With the physical parameters observed in Pas Ipa beach tourism objects, namely the diversity of flora, beach types, depth, slope, accessibility, brightness, beach width and tides. Besides that, the observation of infrastructure was also carried out. The results of the research on the Pas Ipa beach tourism object show that it is very suitable for the land for the Pas Ipa beach tourism object, which is in the S1 category. However, the facilities and infrastructure at Pas Ipa beach tourism objects need to be considered and improved.